2017
DOI: 10.1002/asia.201700696
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mass Signal Amplification and Isotope‐Labeled Alkanethiols for the Multiplexed Detection of miRNAs

Abstract: We report a fast and sensitive method for the multiplexed detection of miRNAs by combining mass signal amplification and isotope-labeled signal reporter molecules. In our strategy, target miRNAs are captured specifically by immobilized DNAs on gold nanoparticles (AuNPs), which carry a large number of small molecules, called amplification tags (Am-tags), as the reporter for the detection of target miRNAs. For multiplexed detection, we designed and synthesized four Am-tags containing 0, 4, 8, 12 isotopes so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…23 In previous MALDI-TOF MS analysis of self-assembled monolayers of alkanethiolates on gold surfaces, oligo EG-containing alkanethiolates were mostly observed as sodium and potassium adducts. [3][4][5][6] In addition, for the analysis of multiple analytes simultaneously, multiple mass tags with different masses should be detected in a narrow mass range without complicated peak overlap. As such, amino acid series mass tags with 14 Da mass differences were used for further feasibility studies.…”
Section: Analytical Methods Papermentioning
confidence: 99%
See 2 more Smart Citations
“…23 In previous MALDI-TOF MS analysis of self-assembled monolayers of alkanethiolates on gold surfaces, oligo EG-containing alkanethiolates were mostly observed as sodium and potassium adducts. [3][4][5][6] In addition, for the analysis of multiple analytes simultaneously, multiple mass tags with different masses should be detected in a narrow mass range without complicated peak overlap. As such, amino acid series mass tags with 14 Da mass differences were used for further feasibility studies.…”
Section: Analytical Methods Papermentioning
confidence: 99%
“…Gildea et al reported an acid-labile trityl protecting group for oligonucleotide synthesis. 20 They introduced the synthetic route for the NHS-activated 4,4 0 -demethoxytrityl chloride (5). The tritylation of the acid-containing thiol with 5 led to the formation of 6, which was subsequently reacted with amine-containing molecules to afford the PMTs (for detailed experimental protocols to prepare the PMTs, see the ESI †).…”
Section: Design Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…It is very challenging to sensitively and specifically detect multiple miRNAs in one pot, not only because miRNAs are in an extremely low concentration and are with short sequence that are susceptible to interference, but also because the multiplexity greatly increases the complexity of detection system. Although various methods such as fluorescence-based approaches have been reported for the detection of miRNAs, these methods suffer from several shortcomings: long detection time and multiple steps (e.g., >3 h), limited sensitivity, or expensive equipment. , This COP method breaks through the bottleneck of existing one-pot technologies, such as CRISPR-Cas-based approaches and Ago-mediated methods , (Table S3), and presents many important and outstanding advantages including the ability of multiplex detection, programmable generality, single nucleotide precision, sensitivity, one-step strategy, simplicity, and rapidness. This method holds great potential in the application of molecular medical diagnosis.…”
mentioning
confidence: 99%